1999
DOI: 10.1002/(sici)1097-4628(19990523)72:8<999::aid-app3>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carboxylic acids on 2-bisbenzothiazole-2,2?- disulfide- and tetramethylthiuram disulfide-accelerated sulfur vulcanization. I. Reaction between the acids and accelerators

Abstract: Benzoic and stearic acids are shown to react with 2-bisbenzothiazole-2,2Ј-disulfide (MBTS) and its polysulfides (MBTP) at vulcanization temperatures to form acid-accelerator complexes 2-benzoylthiobenzothiazole (BzM) and stearicthiobenzothiazole (StM), respectively. At higher temperatures MBTS, MBTP, BzM, and StM are decomposed by the acids. Analogous reactions are observed with tetramethylthiuram disulfide (TMTD) and its polysulfides (TMTP). Lesser amounts of acid-accelerator complexes 2-benzoyldimethyldithio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

1999
1999
2003
2003

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 20 publications
0
31
0
1
Order By: Relevance
“…McGill and Shelver27 observed that, in the absence of rubber, benzoic and stearic acids react with MBTS and its polysulfides (MBTP) at vulcanization temperatures to form the acid‐accelerator complexes 2‐benzoylthiobenzothiazole (BzM) and stearicthiobenzothiazole (StM), respectively. The destruction of MBTP by carboxylic acids will reduce the concentration of accelerator polysulfides (formation of A, Scheme ) available in the compounds and should impact negatively on vulcanization.…”
Section: Resultsmentioning
confidence: 99%
“…McGill and Shelver27 observed that, in the absence of rubber, benzoic and stearic acids react with MBTS and its polysulfides (MBTP) at vulcanization temperatures to form the acid‐accelerator complexes 2‐benzoylthiobenzothiazole (BzM) and stearicthiobenzothiazole (StM), respectively. The destruction of MBTP by carboxylic acids will reduce the concentration of accelerator polysulfides (formation of A, Scheme ) available in the compounds and should impact negatively on vulcanization.…”
Section: Resultsmentioning
confidence: 99%
“…Coleman et al 1 and Dogadkin and Shershnev 2 reported that tetramethylthiuram disulfide (TMTD) degrades to tetramethylthiourea (TMTU) at vulcanization temperatures, while McGill and coworkers [3][4][5][6] reported no such degradation with either tetramethylthiuram monosulfide (TMTM) or TMTD, TMTU forming only at 190°C. It has been suggested that these discrepancies may relate to the presence of an amine impurity that can give rise to a catalytic reaction resulting in the complete decomposition of TMTD to TMTU, the impurity being trapped in closed systems, but escaping from where the system is not completely sealed.…”
Section: Introductionmentioning
confidence: 65%
“…Materials and experimental procedures were detailed in a previous article in this series. 21 Curatives, mixed in an equimolar ratio, were heated in a DSC at 2.5°C/min and analyzed by HPLC at various points along the DSC curve. In the figures, concentrations of the reactants, intermediates, and products are expressed in terms of the initial mol concentration of the reactant.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1 shows that the addition of benzoic acid to an MBTS/sulfur/ZnO mixture at 150°C does not lead to the destruction of MBTP, as occurred with benzoic acid. 21 The MBTP concentration is only slightly (3%) lower than in the absence of benzoic acid. The formation of 2-benzoylthiobenzothiazole (BzM) is difficult to detect and the clearest evidence 21 that there is little interaction between MBTP and ZnO/benzoic acid is the formation of only trace amounts of 2-mercaptobenzothiazole (MBT) ( Fig.…”
Section: Mbts/sulfur/zno/benzoic Acidmentioning
confidence: 99%
See 1 more Smart Citation